Determination of discharge coefficient of rectangular side weirs (2001)
The characteristics of flow over side weirs are taken into consideration to verify the discharge coefficient for suberitical flow conditions under the assumption of constant- specific energy. The main channel discharge, length of weir crest and sill height of the weir are treated as controlled variables. The discharge coefficient Cd is found to depend on the upstream Froude No F1 and also on the ratio of sill height to upstream flow depth S/Y1. Simple linear regression analysis was conducted to establish the relationship of Cd with both F1 and S/Y1 taken separately while multiple regression analysis was conducted to establish the relationship of Cd with both F1 and S/Y1 taken together. Cd decreases with increase in F1 while Cd increases with increase in S/Y1 ratio when taken separately. When taken together, it was clearly evident that variation in Cd was largely due to S/Y1 ratio while the effect of F1 was relatively negligible.